Escape to Murray River - Elmer, Robert (Minneapolis, MN : Bethany House, 1997)
In 1868, after their father is wrongfully convicted and deported on the last prison ship to Australia, twelve-year-old Patrick and the rest of the McWaid family determine to stay together and follow him to the far-off continent.
Keywords: Families -- Ireland -- Fiction; Voyages and travels -- Fiction; Ireland -- Fiction; Australia -- Fiction